15.20.6 problem 6

Internal problem ID [3314]
Book : Differential Equations by Alfred L. Nelson, Karl W. Folley, Max Coral. 3rd ed. DC heath. Boston. 1964
Section : Exercise 38, page 173
Problem number : 6
Date solved : Monday, January 27, 2025 at 07:33:16 AM
CAS classification : [[_homogeneous, `class A`], _rational, _dAlembert]

\begin{align*} y \left (1+{y^{\prime }}^{2}\right )&=2 x y^{\prime } \end{align*}

Solution by Maple

Time used: 0.059 (sec). Leaf size: 67

dsolve((diff(y(x),x)^2+1)*y(x)=2*diff(y(x),x)*x,y(x), singsol=all)
 
\begin{align*} y \left (x \right ) &= -x \\ y \left (x \right ) &= x \\ y \left (x \right ) &= 0 \\ y \left (x \right ) &= \sqrt {c_{1} \left (-2 i x +c_{1} \right )} \\ y \left (x \right ) &= \sqrt {c_{1} \left (2 i x +c_{1} \right )} \\ y \left (x \right ) &= -\sqrt {c_{1} \left (-2 i x +c_{1} \right )} \\ y \left (x \right ) &= -\sqrt {c_{1} \left (2 i x +c_{1} \right )} \\ \end{align*}

Solution by Mathematica

Time used: 3.155 (sec). Leaf size: 64

DSolve[(D[y[x],x]^2+1)*y[x]==2*D[y[x],x]*x,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to -\sqrt {-e^{c_1} \left (-2 x+e^{c_1}\right )} \\ y(x)\to \sqrt {-e^{c_1} \left (-2 x+e^{c_1}\right )} \\ y(x)\to 0 \\ y(x)\to -x \\ y(x)\to x \\ \end{align*}